Public services efficiency provision in italian regions: a non-parametric analysis - Afonso, António (2010)
We measure the performance of public spending in Italian regions regarding the provision of public services, by constructing a so-called total regional performance indicator for strategic sectors such as general administration, energy, water and sewage, solid waste, and transports for 2001. This composite indicator is then the output measure selected to assess expenditure efficiency for the Italian regions, using the non-parametric DEA approach. The computation of efficiency scores allows to rank the regions and to detect some room for improvement in terms of efficiency gains at the regional level.